Some remarks on the rarefaction of the renewal processes - Mogyorödi, J. (Lithuanian Mathematical Journal, 1971)
The abstracts (in two languages) can be found in the pdf file of the article.Original author name(s) and title in Russian and Lithuanian:Ю. Модеруди. Несколько замечаний о разрежении рекуррентных потоковJ. Moderudi. Kelios pastabos apie rekurentinių srautų išretinimą